2004
DOI: 10.3402/ijch.v63i0.17922
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cardiovascular diseases among Swedish Sami — a controlled cohort study

Abstract: Previously reported differences in CVD mortality between Sami and non-Sami, and Sami men and women, can only partly be explained by different exposure to the psychosocial and behaviour risk factors investigated in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 8 publications
5
52
0
1
Order By: Relevance
“…After a complete review of the full articles, 87 studies were excluded because they: (i) did not measure the psychosocial work factors of the DCS and/or ERI models (N=39) (39-77), (ii) did not individually assess exposure to psychosocial factors (N=3) (78)(79)(80), (iii) comprised a population of high school students (not a working population) (N=1) (81), (iv) included <100 participants (N=13) (82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93); (v) were not written in English or French (N=4) (94)(95)(96)(97), (vi) were not published in a peer-reviewed publication (N=16) (11,(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109)(110)(111)(112), (vii) did not measure BP (N=8) (70,(113)(114)(115)(116)(117)(118)(119), or (viii) did not distinctly evaluate exposure to psychosocial work factors (N=3) (120)…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…After a complete review of the full articles, 87 studies were excluded because they: (i) did not measure the psychosocial work factors of the DCS and/or ERI models (N=39) (39-77), (ii) did not individually assess exposure to psychosocial factors (N=3) (78)(79)(80), (iii) comprised a population of high school students (not a working population) (N=1) (81), (iv) included <100 participants (N=13) (82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93); (v) were not written in English or French (N=4) (94)(95)(96)(97), (vi) were not published in a peer-reviewed publication (N=16) (11,(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109)(110)(111)(112), (vii) did not measure BP (N=8) (70,(113)(114)(115)(116)(117)(118)(119), or (viii) did not distinctly evaluate exposure to psychosocial work factors (N=3) (120)…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…As a matter of fact, an underestimation of the prevalence of self-reported MSP symptoms among men was evident during the physical examinations and interviews. Moreover, in a controlled study on a larger population of reindeer herding Sami, we have shown that physical wellbeing is assessed as poor among the herders, particularly among men, indicating dissatisfaction with their physical health (15).…”
Section: Discussionmentioning
confidence: 99%
“…The young Norwegian Sami consume less alcohol than the non-Sami in the same geographical setting, and the young Sami with a more traditional Sami lifestyle have the lowest alcohol consumption (21)(22)(23). No difference in alcohol consumption has been found in Swedish studies of reindeer-herding Sami, other Sami and non-Sami (24,25).…”
Section: Alcoholmentioning
confidence: 97%